Tag Cloud Application and Information Retrieval System: Visualisation to Create Information Literacy - Shri Ram, Shri Ram (DESIDOC journal of library & information technology, 2015)
The purpose of this paper is to discuss the application of tag clouding for information visualisation and information retrieval over social cataloguing tool such as Shelfari (http://shelfari.com). This is a case study where tag cloud is being used as a tool for information visualisation and information retrieval to create awareness about new arrivals in the library. For the purpose of creating awareness amongst the user of the library and promote the use of newly catalogued resources, an online social cataloguing system 'Shelfari' (http://shelfari.com) has been used. The new arrivals are catalogued through social cataloguing system. The Library of Congress subject heading (LCSH) and Medical Subject Headings (MeSH) are being used as tag words for each resource. The tag cloud created in this way has been evaluated for the effectiveness of the social cataloguing. The results suggest that tag clouding helps to create a visual effect and help users to learn about availability of the resources in the library along with the collaborative activities such as reviews and feedbacks, to choose right kind of reading materials. Social cataloguing activities are now getting momentum in online social network system. The use of internet and social network activities are increasing day-by-day so as the use of reviews and feedback for choosing right reading material. This study shall be valuable for those who are interested in choosing right reading materials based on popularity. 10.14429/djlit.35.1.8036